The Effect of Environmental Accounting Disclosure and Good Corporate Governance on Environmental Performance with Financial Performance as a Moderator - Josep Gilbert Ohoitimur; Eva Marin Sambo; Annas Lalo (Golden Ratio of Auditing Research, 2026)
The Effect of Environmental Accounting Disclosure and Good Corporate Governance Mechanisms on Environmental Performance with Financial Performance as a Moderating Variable in Manufacturing Companies Listed on the Indonesia Stock Exchange for the 2021–2023 Period. This study aims to determine and analyze the effect of environmental accounting disclosure and good corporate governance mechanisms on environmental performance and examine the role of financial performance in moderating the relationship. The study was conducted on food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the 2021–2023 period. The research method is quantitative using secondary data with a research population of food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange during 2021–2023 taken through the Indonesia Stock Exchange website, namely www.idx.co.id, the sampling technique used purposive sampling, the number of samples meeting the research criteria was 29 companies that published financial reports and sustainability reports consecutively from 2021–2023 so that 75 data were obtained. The data analysis technique used eviews 12. The results of this study indicate that environmental accounting disclosure has a significant effect on environmental performance, good corporate governance mechanisms have a significant effect on environmental performance, environmental accounting disclosure has a significant effect on environmental performance through financial performance, and good corporate governance mechanisms have a significant effect on environmental performance through financial performance.